The Role of Job Satisfaction Mediating Organizational Commitment Against Employee Performance (Study on Employees of PT BPR Gunung Rizki Semarang) - Ridwan Alfian Noor; Bambang Suko Priyono (Syntax Corporation Indonesia, 2023)
The performance of PT. BPR Gunung Rizki Semarang branch office in 2017-2018 has decreased. This phenomenon was found in the object of research when the preliminary survey was conducted. The results of theoretical studies of factors that can explain performance show results that are still different. Departing from these empirical and theoretical phenomena, this study is aimed at analyzing the effect of Organizational Commitment and Personality on Performance by Mediating Job Satisfaction on employees of PT. BPR Mount Rizki Semarang. The study aims to examine the role of job satisfaction mediating organizational commitment against employee performance. The empirical model developed in this study consists of three research variables, namely organizational commitment and job satisfaction which are thought to explain performance. Research data was obtained through interviews using questionnaires to 124 employee respondents at PT. BPR Mount Rizki Semarang. The collected data were analyzed using multiple regression tests. Statistical test results show that organizational commitment has no significant effect on job satisfaction. While on performance, organizational commitment has a positive effect while job satisfaction has a negative effect.